PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PT SARANA MENARA NUSANTARA TBK - Amelia, Amelia; Puji Muniarty (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the effect of profitability and Firm Size on firm value at PT Sarana Menara Nusantara Tbk for the period 2019–2023. Profitability is proxied by Return on Assets (ROA), Firm Size is measured using the natural logarithm of total assets, and firm value is proxied by Price to Book Value (PBV). This research uses secondary data obtained from annual financial reports. The analytical method used is multiple linear regression analysis with classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation. The results indicate that profitability has a positive and significant effect on firm value. Meanwhile, Firm Size has a positive but insignificant effect. Simultaneously, profitability and Firm Size significantly affect firm value with a coefficient of determination of 78.4%. These findings imply that improving profitability is more effective in increasing firm value compared to merely expanding company size.